2022
DOI: 10.3390/diagnostics12081922
|View full text |Cite
|
Sign up to set email alerts
|

Hirsutism, Normal Androgens and Diagnosis of PCOS

Abstract: Hirsutism is defined as the presence of terminal hair with male pattern distribution in women. While in the general population, hirsutism affects around 4–11% of women, it is the main manifestation of hyperandrogenism in women with polycystic ovary syndrome (PCOS), with a prevalence estimated at 65–75%. Hirsutism in PCOS is associated with both androgen excess and individual response of the pilosebaceous unit to androgens. The modified Ferriman–Gallwey (mFG) scoring system has been widely used in clinical prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 113 publications
1
15
0
Order By: Relevance
“…Our finding is consistent with that by Spritzer et al who was found that androgen hormones were related to the development of hirsutism. 23 Hirsutism can occur if the level of these hormones rises or if the body develops a greater sensitivity to them. PCOS is the most prevalent cause of hirsutism.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding is consistent with that by Spritzer et al who was found that androgen hormones were related to the development of hirsutism. 23 Hirsutism can occur if the level of these hormones rises or if the body develops a greater sensitivity to them. PCOS is the most prevalent cause of hirsutism.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of hirsutism was based on taking a history and performing a clinical examination with the modified Freeman-Galloway rating score, which examines coarse terminal hairs in nine areas of the body including the upper lip, chin, chest, upper and lower abdomen, arms, and thighs. The severity of hirsutism in each section was scored from 0 to 4 26 . In the summation of scores, women with a level ≥ 4 were considered as hirsute 27 .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, there was a significant association of mFG score with androstenedione (A4) and DHEAS from a total of 6,593 PCOS patients distributed across different countries [77]. Using the Rotterdam criteria, US NIH or Androgen Excess Society (AES) criteria, another recent systematic review provided a comprehensive distribution of hirsutism scores in women with PCOS, according to geographic locations [78]. Similar to the different studies, our studies found hirsutism to be a major complaint among medical and dental students.…”
Section: Pcos Among Medical and Dental Studentsmentioning
confidence: 99%